Digital-Based Internationalization Strategy In Penetrating The Global Market: A Case Study On MSMEs Who Are Motorcycle Seat Craftsmen In Mojokerto - Moh. Faizin; Sudarmiatin; Heri Pratikto (Abadi Institute, 2026)
This research aims to analyze the internationalization strategy applied by MSMEs of seat materials